Associação entre sobrecarga e as características sociodemográficas e clinicas do cuidador familiar de pessoas em hemodiálise - Samantha Vieira Alves Amaral (2022)
Introduction: Hemodialysis treatment generates many changes in both the patient's life and that of his/her family caregiver, thus increasing the responsibilities and demand for care, which may lead to mental and physical illness, causing overload. Objective: To associate burden with sociodemographic, clinical and behavioral characteristics of family caregivers of people on hemodialysis. Method: Cross-sectional study, carried out with 73 family caregivers of people on hemodialysis in two dialysis centers in the city of Belo Horizonte/Minas Gerais, year 2021. The caregiver burden was measured using the ZBI-12 instrument. To compare the level of burden between the categories of a variable, Pearson's Chi-Square test was used. In comparing the overall burden score between groups, the Student t-test and the F ANOVA (parametric approach for comparing two groups or more than two groups, respectively) or the KruskalWallis (nonparametric approach for comparing two) tests were used. or more groups). The methods used for multiple comparison were Tukey and Dunn, for the parametric and nonparametric approaches respectively. The verification of the normal distribution assumption for the overload data was performed using the Shapiro-Wilk test. All analyzes used a 95% confidence level for interval estimates and a 5% significance level for hypothesis testing. Data analysis was performed in the R statistical programming environment (R Core Team, 2015). Results: It is noted that most caregivers are female 62 (84.9%), married 41 (56.2%) and housewife 29 (39.7%). The average income was between two and three minimum wages, 48 (65 .8%) participants used any continuous medication and 58 (79%) participants said they did not use antidepressants and/or anxiolytics. The most frequent degree of kinship reported by the participants was that of a spouse 29 (39.7%), followed by that of a child 27 (37%), 47 (64.4%) people declare that they provide care for a period of 4 to 8 hours a day, and 19 (26%) with a workload of more than 8 hours a day. In addition, 60 (82.2%) people said they did not receive financial assistance from other sources. Regarding the level of burden 59 (80.8%) of caregivers had levels of burden considered high. The two variables that were statistically associated with burden were occupation (p-value = 0.022) so that retired and home caregivers had high burden, and the use of antidepressants and/or anxiolytics (p-value = 0.008) so that caregivers who used such medications had a high burden. Conclusion: It is concluded that family caregivers of the person on hemodialysis had a high burden, and the occupation and use of antidepressants and/or anxiolytics by the caregiver were significantly associated with burden